Nanotube surfactant design the versatility of water-soluble perylene bisimides - Backes, Claudia (Advanced materials (Deerfield Beach, Fla.), 2010)
The synthesis of perylene-based single-walled carbon nanotube (SWCNT) surfactants and the dispersion and exfoliation of SWCNTs in water by a variety of designed surfactants is investigated. The quality of the nanotube dispersions is evaluated by optical absorption and emission spectroscopy, zeta-potential measurements and statistical atomic force microscopy (AFM). Significantly the dispersion efficiency can be increased at higher pH, as water solubility of the surfactants is ensured by peripheral derivatization with carboxyl-functionalized first- and second-order Newkome dendrimers. Even at very low perylene concentrations of 0.1 g L(-1) and a nanotube-to-surfactant ratio of 1:1, the nanotube supernatant after centrifugation contains up to 73% of the pristine material with exfoliation degrees (the number of fractions of individualized nanotubes N(I)/N(T)) of up to 76%. The adsorption of the perylene core to the nanotube scaffold is indicated by red-shifted perylene-absorption and SWCNT-emission features except for the smallest perylene amphiphile, where solubilization is presumably based on a micellar arrangement. The nanotube fluorescence is significantly altered and reduced in intensity compared to nanotubes dispersed in sodium dodecylbenzene sulfonate (SDBS) being strongly dependent on the structure of the perylene surfactant. We attribute this observation to the homogeneity of the surfactant coverage, e.g., the supramolecular arrangement onto the nanotube backbone. This study represents a step forward in understanding the structure-property relationship of nanotube surfactants. Furthermore high-quality nanotube dispersions with increased degrees of exfoliation are highly desirable, as the efficiency of nanotube separation techniques relies on highly individualized samples